ANALISIS TINGKAT LAYANAN SERTA PROSEDUR KREDITUR TERHADAP PENGAMBILAN KEPUTUSAN KREDITUR BANK SULSELBAR CABANG PANGKAJE’NE KEPULAUAN - Nurhaedah Nurhaedah (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2018)
The purpose of this research is to know the influence of the level of service as well as a credit Against the decision-making procedures of the lender Bank Sulselbar branch of the Pangkaje'ne Islands.The population in the penelitiann this is the customer on the last year in April 2017 April 2018 until on Bank Sulselbar branch of the Pangka'jene Islands with total sample as many as 80 people customer. Method of data collection in this study is a questionnaire, interviews and documentation. Methods of data analysis using descriptive and quantitative methods i.e. using multiple linear regression analysis to measure the influence of level of service as well as the procedure of Creditors Against the creditor Bank Decision-making Sulselbar Sulselbar The branch of Pangkaje'ne Islands. Based on testing the free variables of table F (level of service as well as the procedure of creditors) jointly have a positive and significant influence against variables bound i.e. lender decision making.Through testing (R) correlation coefficient obtained that level of service as well as the procedure of creditors against the decision of taking the lender Bank Sulselbar Sulselbar Branch Pangkaje'ne Islands is a high relationship of 61.8%.With the level of service is the most dominant factor in influencing decision-taking Bank credit Sulselbar branch of the Pangkaje'ne Islands.